Tadpoles respond to background colour under threat - Eterovick, Paula Cabral (Sci Rep, 2018)
The ability to respond to background colour is an important feature of species that might benefit from background matching camouflage. Tadpole colour patterns vary and could be associated with several functions, including defense. Because tadpoles are exposed to a wide array of visually oriented predators, they represent good models to study defensive colouration and associated behaviours. We tested whether a potentially disruptively camouflaged tadpole with a dark body crossed by yellow bars (Ololygon machadoi) is able to respond differently to matching light and dark natural background colours and an artificial blue contrasting background. We used a syntopic contrasting black tadpole (Bokermannohyla martinsi) as a control, expecting it not to respond to background colour in search for camouflage. Ololygon machadoi tadpoles chose light over blue backgrounds under threat, as expected, however they did not show preferential use of dark vs. blue backgrounds. Bokermannohyla martinsi did not respond to any combination of background colours. Our results suggest that O. machadoi tadpoles are able to respond to background colour, and may favor matching backgrounds under some circumstances. The potentially disruptive colouration of O. machadoi tadpoles may increase their repertoire of escape strategies, background matching being one of the options to escape predation.